A Novel Low Power-Application UPS consisting of an APF - Correction circuit & integrated Battery-Management system - Venkat Gumpini; O. Chandra shekar (Institute of Advanced Engineering and Science, 2018)
For the up-coming generations of power-supply systems, the load located area power-supply sources are an effective one, in terms of our requirements: simplicity, integrity, battery-backup, etc. This could follow the Normalization of power factor & Reducing THD% values on input current, which makes us to add an essential to include a power-factor correction unit at supply side in these new typical topologies. This Proposed architecture presents an integrated battery manage system which can also offers PF correction along with Galvanic-Isolation of battery in a humble single structure. [3] The proposed scheme has the reliable characters like increased efficiency, compact circuit and reduced costs associated with a traditional standalone multiple-stages UPS with PFC. This paper addresses the UPS action, the analysis and simulation results of Proposed UPS scheme.